Scaffolding inquiry-based STEM: Enhancing problem-solving skills of preservice biology teachers - Dwi Purbowati; Paidi Paidi; Anna Rakhmawati (Biosfer: Jurnal Pendidikan Biologi, 2026)
Ecology courses demand the capacity to analyze complex environmental phenomena and to design innovative solutions. However, conventional ecology lectures often lack structured guidance to develop problem-solving skills. This research aims to evaluates the impact of inquiry-based STEM learning with scaffolding on the problem solving skills of prospective biology teachers, focusing on the eutrophicated Cengklik Reservoir ecosystem. Employing a quasi-experimental pretest-posttest control group design, the sample consisted of  60 students, divided into an experimental group (n=30) received inquiry-based STEM with scaffolding and a control group (n=30) receiving standard inquiry. The experimental group designed a five-layer water filtration device as their engineering solution.  Quantitative data were analyzed using ANCOVA with pretest scores as a covariate,  partial eta squared (η²) as the effect size, and were integrated with qualitative interview data. The results indicate significant difference in problem solving skills between groups (F(1,57)=24.356; p<0.001; η²=0.391), with the experimental group achieving a higher results (adjusted mean=3.74) than the control group (adjusted mean=3.03). The developed five layer filtration device reduced water turbidity (89.7%) and effectively bridged ecological theory with engineering practice. Thus, results demonstrate that inquiry-based STEM with enhances problem-solving capabilities through authentic product design. It is recommended that biology teacher education programs systematically integrate scaffolded STEM frameworks into ecological and environmental curricula to better prepare candidates for addressing real-world socio-scientific challenges.